Listening Made Easy: The Impact of Conversational Videos on Students’ Listening Comprehension - Muhammad Arbain; Fitra Ramadani; Novika Hartatya (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2023)
Using video material for teaching listening is advantageous because it provides rich resources for English dialogue and pronunciation practice. This widespread use of video materials supports the development of listening skills in English language learning. In this study, the researcher focuses on using English conversation videos, specifically tailored to the topics covered in the 8th grade junior high school curriculum. The aim is to help students better understand functional English conversations, thereby achieving the learning objectives more effectively. This research is intended to investigate the difference of result between the student who are taught listening comprehension using conversation video and those who are taught listening comprehension without conversation video. The findings shows that the average post-test score in the Experimental Class was 68.84, whereas the average post-test score in the Control Class was 65.08These results indicate that the use of conversation videos significantly enhances students’ listening comprehension, suggesting that this teaching method can be an effective alternative in English language learning. This research is expected to contribute to the development of more innovative and engaging teaching methods for listening skill in the classroom.